Foreign experience of legal regulation of the general aviation: perspectives for Ukraine - Зуєва, Вікторія Олександрівна; Череватюк, Вікторія Богданівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2013)
In the article the authors refer to the study of foreign experience in the legal regulation of the general aviation. An attempt was made to find possible areas for its use to improve the effectiveness of legal regulation of AGD in Ukraine.